Knowledge Level of Basic Life Support for Students and Staff at Senior High School Al-Azhar Asy Syarif Islamic Boarding School Deli Serdang, North Sumatra - Primaputra Lubis, Andriamuri; Irina, Rr. Sinta (Talenta Publisher, 2023)
Background: Basic life support is an emergency action that can be done by ordinary people to free the airway, help to breathe and maintain blood circulation without using aids. Knowledge of basic life support (BLS) is a knowledge and skill because if you only know the theory without doing training or practice, then the motivation to help becomes lacking and mentally untrained when dealing with real events. Purpose: To determine the level of knowledge of students and staff of Madrasah Aliyah Al-Azhar Asy Syarif Islamic Boarding School Deli Serdang about BLS. Method: The design used in this study is a cross-sectional method. Data collection was in the form of a questionnaire containing questions about BLS training. Questionnaire collection was carried out twice, namely the pretest which was carried out before the BLS material and training were given by the instructor and the posttest which was carried out after the BLS material and training were given. Results: Respondents' post-test scores obtained fewer values, 5 respondents (4.24%) had enough values, and 113 respondents (95.76%) had good scores. It was found that respondents got quite a good score after training on BLS. Conclusion: Based on the level of knowledge of students and staff at MA Al-Azhar Asy Syarif Islamic Boarding School Deli Serdang about BLS, it is included in the good category.